Modeling of Tissue Laser Irradiation in Cylindrical Coordinates Using the Finite Pointset Method - KORCZAK, Anna; SAUCEDO-ZENDEJO, Felix R. (Computer Assisted Methods in Engineering and Science, 2025)
This study focuses on a numerical analysis of heat transfer in biological tissue. The proposed model is formulated using the Pennes equation under transient conditions within a two-dimensional (2D) cylindrical domain. The tissue undergoes laser irradiation, with internal heat sources determined based on the Beer–Lambert law. Moreover, key parameters, including the perfusion rate and effective scattering coefficient, are modeled as functions dependent on tissue damage. Numerical computations are performed using the finite pointset method (FPM). The findings, discussed in the final section, indicate that the FPM approach is a viable and effective tool for analyzing thermal processes in biological tissues.